Do Women Panic More Than Men? An Experimental Study on Financial Decision - Hubert J. Kiss; Ismael Rodriguez-Lara; Alfonso Rosa-Garcia (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
We report experimental evidence on gender differences in financial decision that involves three depositors choosing between waiting or withdrawing their money from a common bank. We find that the position in the line, the fact of being observed and the observed decisions are key determinants to explain subjects' behavior. Although both men and women value being observed, it has a greater effect on womens decisions. Observing a withdrawal increases the likelihood of withdrawal but women and men do not react differently to what is observed, so they are equally likely to panic if a bank run is already underway. Interestingly, risk aversion has no predictive power on depositors' behavior.
Keywords: C91; D03; D8; G02; J16; 330; bank run; gender difference; strategic uncertainty; experimental evidence; coordination